The Effect of Job Characteristics towards the Organizational Commitment of the Employees - Ramli, Yanto; Soelton, Mochamad; ., Paijan; Khotimah, Nurul (International Journal of Emerging Trends in Social Sciences, 2020)
Organization today are facing both the development of the fourth industrial revolution, also known as Industry 4.0 and also the implication of millennial workforce. The objective of this research is to analyze and develop the human resource management in the organization in order to find out the engagement of the millennial workforce commitment to the organization and to find out the impact of the employee turnover intention within the organization. The research in done through the distribution of questionnaire, and the population of this research is consisted of the employees in a local IT provider company in Jakarta, Indonesia. This research is performed by using descriptive and verification method, the descriptive method is based on observation analysis and the verification method is based on quantitative analysis. The sample determination was done through Non-Probability (Random Sampling) and the tool of analysis is using Partial Least Square (PLS). The population of this research is based on 350 employees of an IT provider company in Jakarta, Indonesia. The result indicated that job characteristics have higher significant influence on organizational commitment compared to career development that effect the turnover intention of employees. Organizational commitment has a significant effect on employee turnover intention. This means that in order to counter the turnover intention of the millennial employees, the organization must develop proper job characteristics to suit the millennial workforce which might be useful to help overcome the research phenomenon.